PERBANDINGAN KADAR NIPAGIN PADA KECAP MIE INSTAN DAN KECAP BOTOLAN YANG DIPERJUALBELIKAN DI KOTA MAKASSAR - Rahmawati Rahmawati; Anita Anita; Rezky Marwah Ulfa (Poltekkes Kemenkes Pakassar, 2019)
Nipagin is a preservative that is allowed to use in food, but the levels should not exceed the maximum limit set by Permenkes RI No. 722 / Menkes / Per / IX / 88 about food additives that is 250 mg / kg. The purpose of this study was to determine the nipagin content contained in instant noodle soy sauce and bottled soy sauce in Makassar city using spectrophotometer uv-vis method using deniges and sodium nitrite 2% reagent. The results showed that the results of nipagin content ratio in soybean noodles and bottled soy sauce by UV-VIS spectrophotometer, soy noodle samples (A) were obtained at 0.0105 mg / g nipagin, 0.0135 mg / g noodle soy sauce, Soy noodles (D) 0.0108 mg / g, soy noodles (D) 0.012 mg / g, soy noodles (E) 0.0073 mg / g, soy sauce (A) 0.0182 mg / g, bottled soy sauce (B) ) 0.0079 mg / g, soy sauce (C) 0.01 mg / g, soy sauce (D) 0.0071 mg / g, soy sauce (E) 0.0152 mg / g. Positive contains nipagin when the color change becomes pink. The pink color formed measured its absorbance at a wavelength of 504 nm. The calibration curve was made in concentrations of 0, 15, 20, 22, 25, and 30 mg / ml and obtained the regression equation Y = 0.0022x-0.0017. The result of data analysis using t-test obtained p = 0,73> 0,05 meaning Ho accepted and Ha rejected, while result of manual analysis obtained by t-count (-0,3706) <t table (2,262), so it can be concluded that There was no significant difference between nipagin content of instant noodle soy sauce and bottled soy sauce. . Keywords: soy sauce, preservative, nipagin, spectrophotometer uv-vis